2006
DOI: 10.1254/jphs.fp0050711
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clarithromycin on the Pharmacokinetics of Cabergoline in Healthy Controls and in Patients With Parkinson’s Disease

Abstract: Abstract. Cabergoline is used in the treatment of Parkinson's disease (PD). Clarithromycin is a potent inhibitor of CYP3A4 and P-glycoprotein and is often co-administered with cabergoline in usual clinical practice. We studied the effect of clarithromycin co-administration on the blood concentration of cabergoline in healthy male volunteers and in PD patients. Study 1: Ten healthy male volunteers were enrolled and were randomized to take a single oral dose of cabergoline (1 mg / day) for 6 days or a single ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 25 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…In one case, a 300% increase in cabergoline concentration without associated toxicity was reported, and in the second, cabergoline toxicity in the form of hyperkinesia requiring cabergoline dose reduction subsequently occurred. In the second paper, a pharmacokinetic study evaluating co‐administration of clarithromycin and cabergoline in ten healthy adults and seven patients with PD demonstrated that clarithromycin resulted in mean cabergoline concentration increases to about 2.6‐fold and 1.7‐fold in healthy volunteers and PD patients respectively . There was no dose‐related adverse event reported in this paper, however, three of seven PD patients experienced improvement in parkinsonian symptoms.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In one case, a 300% increase in cabergoline concentration without associated toxicity was reported, and in the second, cabergoline toxicity in the form of hyperkinesia requiring cabergoline dose reduction subsequently occurred. In the second paper, a pharmacokinetic study evaluating co‐administration of clarithromycin and cabergoline in ten healthy adults and seven patients with PD demonstrated that clarithromycin resulted in mean cabergoline concentration increases to about 2.6‐fold and 1.7‐fold in healthy volunteers and PD patients respectively . There was no dose‐related adverse event reported in this paper, however, three of seven PD patients experienced improvement in parkinsonian symptoms.…”
Section: Discussionmentioning
confidence: 63%
“…There was no dose‐related adverse event reported in this paper, however, three of seven PD patients experienced improvement in parkinsonian symptoms. While investigators of these reports attribute the mechanism of interaction as itraconazole/clarithromycin‐mediated inhibition of the CYP3A4 metabolism of cabergoline, it has subsequently been hypothesized to have occurred as a result of inhibition of the P‐gp transporter (a transporter which both clarithromycin and itraconazole are known to inhibit), which is responsible for the efflux of cabergoline from the CNS .…”
Section: Discussionmentioning
confidence: 99%
“…Cabergoline PK was studied in 10 healthy volunteers and 7 Parkinson patients after co-administration of CLR. This resulted in an increase of both the AUC and C max of cabergoline by 260% in healthy volunteers and by 170% in Parkinson patients [232]. When ERY was co-administered with roflumilast, the AUC of the latter increased by 70% in an open-label single-dose comparative study of 16 healthy subjects [233].…”
Section: Resultsmentioning
confidence: 99%
“…The cardinal treatment for patients with PD is oral administration of levodopa with peripheral decarboxylase inhibitor (DCI). 1 There are two DCI in clinical use: benserazide and carbidopa. In combination with levodopa, they are generally regarded as equally effective.…”
Section: Introductionmentioning
confidence: 99%